Dermatoglyphics in infants with isolated, non-familial cleft lip palate- a case control study from Southern India - Anish, Lia Sarah; S. G., Sowmya; Shenoy, Rathika; Shetty, Vikram (International Journal of Contemporary Pediatrics, 2017)
Background: The role of genetic factors may be established by study of dermatoglyphics, therefore, any genetic abnormality during the formation of cleft lip and/or palate (CL/P) in the early trimester maybe reflected by altered dermatoglyphics. Aim: This study aims to assess altered dermatoglyphics in children with isolated, non-familial CL/P to understand the role of genetic factors in clefting. Methods: Case control study in a cranio-facial centre comprising of 40 infants (6-9 months) with CL/P and age and gender matched controls. Finger printing was done using black duplicating ink. A p-value of 0.05 was considered significant. Results: Majority (57.5%) had left sided clefting. Ulnar loops were the predominant digital pattern in the study group but there was no statistical difference with the controls, when all the finger patterns were considered together. There was significant difference in digital patterns in between the left thumb (p=0.033), ring (p=0.048) and little fingers (p=0.029) in the two groups. Comparison between the right and left hands within the study group showed significant difference in digital patterns in the thumb (p=0.047) and little finger (p<0.001). The study group also had a wider atd angle with significance (right hand p=0.038, left p=0.003) and a lower a-b ridge count with significance (right hand p= 0.045, left p=0.012). Conclusions: There was a definite dermatoglyphic difference specifically in the left hand, which was also the major side of clefting, within subjects as well as between subjects and controls.